IMPLEMENTASI METODE IQRO’ DALAM PENGENALAN HURUF HIJAIYAH PADA SISWA RA PERWANIDA II MATARAM - Anggun Nirmala Sari; Djuaini Djuaini; Muammar Qadafi (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2020)
This study aims to determine how the implementation of the Iqro’ method in introducinghijaiyah letters at the 4-5 years age students in RA Perwanida II Mataram. This studyused a descriptive qualitative research approach in order to obtain broad and in-depthinformation about purpose of the study. The data source in this study were the principalof RA Perwanida II Mataram, teachers of group A class students, parents of group Astudents. The data collection used observation, interview, and documentation. Theresults showed that the implementation of the Iqro’ method in introducing the hijaiyahletters in children consisted of planning, implementation, and evaluation. The use of theiqro’ method provides a basic understanding of the hijaiyah letters and the ease ofdistinguishing letters properly and correctly, both sequentially and randomly. The iqro’method also has advantages, such as it is easy to understand and use, while thedisadvantages are that it cannot be read with tartil rhythms and is not taught tajwidreadings.